EURAD State-of-the-Art Report: Assessment of the chemical evolution at the disposal cell scale – part II – gaining insights into the geochemical evolution - Deissmann, Guido; Neeft, Erika; Jacques, Diederik (Frontiers in Nuclear Engineering, 2025)
Long time frames are to be considered in the safety and performance assessment of deep geological disposal of intermediate and high level radioactive waste. Geochemical conditions will change in the waste, conditioning matrix, waste package, engineered barriers and the host rock–all components present at the disposal cell scale. This aspect of geological disposal was the focus of the work package ACED (Assessment of chemical evolution of intermediate level (ILW) and high level (HLW) waste at disposal cell scale) in the EURAD project (the European Joint Programme on Radioactive Waste Management). The first part of this review provided a narrative of the geochemical evolution of the disposal cell. In this second part, an overview is given about methods and approaches that can be used to gain further insights into the processes driving the geochemical evolution, more in particular (i) laboratory and in-situ experiments, (ii) archaeological and natural analogues, and (iii) modelling tools. The review concludes with a short discussion on the consequences on material properties, waste forms and radionuclide mobility.